(untitled) (GAIMS Journal of Medical Sciences, 2024)
Background: Literature supports that for overall development of mental as well as physical health and academic success, working memory is an important necessity. Low childhood Socioeconomic status (SES) negatively affects the development of cognitive functions. Right nostril yoga breathing (RNB) and alternate nose breathing (ANB) are fairly simple and children can be taught to do this with practice easily. Material and Methods: It was a randomized pre -post study with a total of 48 students (25 boys & 23 girls) in an age group between 10 to 14 years. Each group comprising of 24 students were assigned to do RNB and ANB for 30 days. Model based on The Wechsler Intelligence scale for children in native language was used to test the working memory of the students before and after 30 days intervention. Results: Average age of the students was 13.10 years. Modified B. G. Prasad was used to define socioeconomic status and all fitted into the Lower Socioeconomic class. There was an improvement in all the three subsets of working memory in the post test score of both the group. Using Cohen’s D analysis, the effect size was large for Digi Span Forward with both RNB and ANB intervention (1.12 vs 1.16) Both practices showed a medium effect size on Digi Span Backward assessment (1.41 vs 1.20). In the more complex Letter Number Sequencing assessment , the effect size was larger after practicing ANB and medium after practicing RNB (1.16 vs 0.91). Conclusions: Support in the form of this inexpensive, simple intervention like yogic breathing techniques might help to improve the working memory skills among these impoverished children who have too many environmental and social stressors hampering their cognition.